Epidemiological aspects of osteoporosis - Walker-Bone, K; Arden, N; Cooper, C (1998)
Osteoporosis is an increasing social and economic burden as the age of populations throughout the world increases. The purpose of this review is to highlight some of the key epidemiological aspects of osteoporosis. First, the definition is explored, examining its origins, implications and limitations. The clinical significance of osteoporosis lies in its predisposition to fracture, but once fracture has occurred, intervention is already late. As a result, methods of noninvasive assessment have been developed which can be used to identify 'at risk' subjects. An overview is given of the densitometric WHO criteria which are used to define these high risk populations, and their limitations are explored, including: significant overlap between normal and fracture-prone groups; applicability in individuals; variations between populations; and inaccuracies which are inherent in measurement with any equipment. These variations are summarized for the sites which are most frequently affected by osteoporotic fractures, particularly at the hip, spine and wrist. Finally, using current epidemiological knowledge, and estimates of likely demographic changes, future projections for fracture are estimated.